Assessment of plasma blood sugar level in first degree relatives of known type 2 diabetes patients: a descriptive study from Maharashtra, India - Deshmukh, J. K.; Mulay, P. Y.; Naghate, Amit G.; Takalkar, Anant A. (International Journal of Advances in Medicine, 2020)
Background: There is steady increase in the prevalence of diabetes mellitus from 0.73% to current 2.4% in rural and 4.0% to 11.6% in urban areas. Familial clustering of diabetes may support a genetic predisposition to diabetes. With increase in the prevalence of diabetes there is increase in number of first degree relative as well, thus an increased risk of developing diabetes, will also increase. To study the plasma glucose levels in First-degree relatives of family member of type 2 diabetic patients was the objective of the present study. Methods: It is a descriptive observational study with 1020 individuals serially coming to our outpatient Department for Pre-employment Medical Health Check Up Annual Health Check Up were selected. These individuals have been enrolled for the study and their family history of diabetes was noted, their sugar levels and their lipid levels were estimated and their body mass index was calculated. The data thus collected and analyzed with excel. Results: 184 (18%) individuals were FDRs, were as 836 (82%) individuals were Non-FDRs. There were 754 (74%) males [131(17%) FDR and 623(83%) Non-FDR], were as 213 (26%) females [53(20%) FDR and 213(80%) Non-FDR], 61(6%) individuals were having Diabetic Mother, 91(9%) individuals had Diabetic Father and 32(3%) were those in whom both the Parents were Diabetic. It was found that maternal history has strong association for getting abnormal BSL levels as compared to a diabetic father as the RR of 9.82 (95% 4.84 to 19.95) in individuals with mother being diabetic, and RR of 1.54(95% 0.68 to 3.87) of father being diabetic. Conclusions: Family history of diabetes, maternal history of diabetes and history of both the parents having diabetes are risk factors for diabetes in FDRs.